Contrasting and Evaluating Different Clustering Algorithms: A Literature Review - Joshi, Swati; Khan, Farhat Ullah; Thakur, Narina (International Journal of Computer Sciences and Engineering, 2014)
Clustering is a practice of splitting data into set of analogous objects; these sets are identified as clusters. Each cluster comprised of points that are alike among them and unalike compared to points of other cluster. This paper is being set to study and put side by side different data clustering algorithms. The algorithms under exploration are: k-means algorithm, hierarchical clustering algorithm, k-medoids algorithm, and density based algorithms. All these algorithms are analyzed on R-tool by taking same data-set under observation.